Kandungan Vitamin C Dan Kualitas Pada Selai Kulit Buah Pisang Ambon Dengan Penambahan Buah Stroberi Dan Mahkota Bunga Sepatu - Arti, Marizka Putri Setyawana; , Dra. Aminah Asngad, M.Si (2015)
One of jam raw product innovation which is ambon's banana skin. ambon's banana skin contains protein, fat, pati, ash, fiber as olahan jam food. To the effect this research mengetahuibkandungan vitamin c and organoleptik's quiz on bananas skinned jam ambon with added numbers stroberi and shoed flower calyx. This observational method Fledged Random Design (RAL) by use of two factors, namely heavy shoed flower (0,50,100 grams) and stroberi's fruit weight( 0,50,100 grams) with two times dry run. Result observationaling to point out that shoed flower calyx weight and heavy numbers stroberi regards to titrate vitamin c jam curries ambon's banana. Conclusion from peneltian jam curries ambon's banana namely heavy numbers stroberi and calyx heavy influential shoed flower to titrate vitamin c on bananas skinned jam ambon. This jam have vitamin rate c supreme available on conduct d. 2 S 2 as much 48,05 mg / 100g by added numbers stroberi and stroberi's flower calyx 100 grams and vitamins c bottommost as much 22,53mg / 100g with neither added numbers stroberi and also without shoed flower calyxs. Bananas skinned jam ambon has to ruddle, delicious aroma, viscous texture and a real treat.